Unconfined propeller jet scour on clay/sand mixtures - Cihan, Kubilay; Dog, Ali; Yilmaz, Damla; Ozan, Ayse Yuksel; Yildiz, Osman; Sahin, Cihan (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
In this study, scour due to an unconfined propeller water jet on homogeneous clay-sand mixtures was investigated experimentally. A total of 9 tests were conducted for the sand bed and 18 tests were carried out for the sand-clay mixture bed. Since clay contents (p) of 0, 5 and 10% by weight were used in the experiments, scour in poorly cohesive sand-clay mixture bed was taken into account. Propeller diameters (Dp) were 0.06 and 0.09 m. Dimensionless propeller heights (y0/Dp) were defined as 1.67, 1.11, 1.0. The increase in clay content causes a decrease in the scour depth and changes the formation of scour profiles. The parameters y0/Dp, F0 (densimetric Froude number), p were found to have significant effects on the behavior of clay-sand mixtures. Considering the test results, equations were proposed to estimate the maximum depth and length of the scour hole formed in the equilibrium condition. In addition, by modifying the equation proposed by Hong et al. (2013), a new equation is proposed for the estimation of temporal maximum scour depth due to the propeller water jet on the sand and weakly cohesive sand-clay mixture beds.
Keywords: Clay-sand mixture; Unconfined propeller jet; Scour; COHESIVE SOIL; Engineering; Oceanography